Pendidikan Kampung Anti-Politik Uang dalam Pemilihan Umum 2024 di Kota Salatiga (Studi Kasus Rw 4, Desa Ngronggo, Kelurahan Kumpulrejo, Kecamatan Argomulyo) - N, Samuel Adrian Oscananda (Jurnal Ilmiah Widya Sosiopolitika; Vol 6 No 2 (2024): ISU-ISU PEMBANGUNANDO - 10.24843/JIWSP.2024.v06.i02.p01, 2025)
Money politics is a persistent issue during general elections and negatively impacts democracy in Indonesia. This study aims to: (1) analyze the implementation process of the Anti-Money Politics Village Education Program (KAPU) during the 2024 General Election in RW 4, Kampung Ngronggo, Kumpulrejo Village, Argomulyo District, Salatiga City; and (2) identify the factors influencing the effectiveness of the program. A qualitative method with a descriptive approach was employed to provide an in-depth understanding of the phenomenon. Data were collected through interviews with key figures, including the head of Bawaslu Salatiga City, Muhdi, and the head of RW 4 Ngronggo, alongside documentation to supplement the findings. The theoretical framework combines Van Meter and Van Horn's policy implementation theory and Pierre Bourdieu's social capital theory, particularly using the verstehen approach to understand the role of social capital in political education. The findings suggest that while the Anti-Money Politics Village Program has been effective in raising awareness, its success is hindered by various social and economic factors. Overall, the KAPU education initiative in Ngronggo Hamlet has progressed well and contributed to reducing money politics in the community.